Safety and compliance among newly qualified paramedics in a pre-hospital clinical trial of an investigational medicinal product: a post-hoc analysis of the PACKMaN randomised controlled trial. - Rosser, Andy; Gunson, Imogen; Green, Zoe; Lall, Ranjit; Michelet, Felix; Miller, Elisha; Miller, Joshua; Noordali, Hannah; Perkins, Gavin; Stanley, Owen; Smyth, Michael (British Paramedic Journal, 2025)
Introduction: Pre-hospital research has unique challenges. Ambulance clinicians are required to enrol patients in research trials during emergency situations, often remote from the research team at time of recruitment. As newly qualified paramedics (NQPs) represent a significant and growing proportion of ambulance clinicians, it is important to establish whether they can safely and effectively recruit patients to clinical trials. This article reports a post-hoc analysis of the PACKMaN trial, a large, double-blind randomised controlled trial of an investigational medicinal product of ketamine versus morphine in the pre-hospital setting. Methods: Adverse events (AEs) and serious adverse events (SAEs) experienced by patients recruited to the PACKMaN trial, as well as protocol non-compliances (NCs) experienced by paramedics during the trial, were retrospectively analysed. We compared recruitment, incidence and type of AE, as well as incidence of SAEs and NCs dichotomised by paramedic experience. Results: Of the 458 patients, 259 (56.6%) and 199 (43.4%) were recruited by experienced paramedics and NQPs, respectively. Incidence of AEs was similar regardless of experience: experienced paramedics reported 128/259 (49.8%) and NQPs reported 91/199 (45.7%) (OR 0.86 95% CI [0.60-1.25]). Incidence of SAEs were slightly increased in the NQP group (8/199 (4.0%)), compared to experienced paramedics (4/259 (1.5%)); however, this was not statistically significant (OR 2.67, 95% CI [0.66-9.00]). NC was similar in both groups: experienced paramedics 3/259 (1.2%) and NQPs 6/199 (3.0%) (OR 2.65 95% CI [0.66-10.74]). Conclusion: In a double-blind controlled trial of an investigational medicinal product, there was no statistical difference in the incidence of AEs or NCs between NQPs and experienced paramedics. NQPs made an important contribution to patient recruitment in this study, improving the generalisability. SAEs and NCs were rare, and patients received analgesics safely. There was no correlation between experience and AE likelihood, and no safety concerns identified arising from NQP participation. Our findings demonstrate that NQPs can safely recruit patients to clinical trials.